THE OPINIONS OF PRIVATE SCHOOL TEACHERS TO THE SCHOOL ADMINISTRATION USING THE PRINCIPLES OF GOOD GOVERNANCE PRINCIPLES OF THE ADMINISTRATORS, SAMUTPRAKARN PROVINCIAL EDUCATION OFFICE - Srirat , Atchima; Yapradit, Sumitra (Journal of MCU Nakhondhat, 2023)
The objectives of this research were as follows: 1) to assess the level of school administration, based on the principles of good governance, among administrators; 2) to compare school administration, utilizing the principles of good governance, among administrators classified by sex, educational background, age, work experience, and school size; and 3) to formulate recommendations for school administration, guided by the principles of good governance, among administrators. The research employed interviews with 5 school administrators and utilized quantitative research methods. A questionnaire was administered to a sample of 351 participants, and descriptive statistics including mean and standard deviation were applied. Hypothesis testing was conducted through T-value and F-value testing. The results indicated the following: 1) The level of comparison with the principles of good governance among the target group was rated as very high ( = 3.85). 2) When comparing the administration of educational institutions using the principles of good governance among administrators classified by sex and age variables, the overall picture is not different. However, the qualification variable, work experience, and the size of the educational institutions show differences. 3) Compiling recommendations for school administration based on the principles of governance among administrators revealed that three aspects had the lowest average and should be developed. These aspects are as follows: 1) Participation, 2) Consensus Oriented, and 3) Accountability.